Intestinal permeability of agaro-oligosaccharides: Transport across Caco-2 cell monolayers and pharmacokinetics in rats - Shirai, Ikuya; Karasawa, Koji; Kodaira, Yusuke; Iwasaki, Yu; Shigemura, Yasutaka; Makabe, Hidefumi; Katayama, Shigeru (Frontiers in Nutrition, 2022)
Agaro-oligosaccharides (AOSs), even-numbered oligosaccharides prepared from agar, are applied to various food, including supplements, drinks, and jellies because of their biological activities. This study aimed to elucidate the AOS permeation in the gastrointestinal tract in vivo and in vitro. Agarobiose, agarotetraose, and agarohexaose were detected in rat plasma after oral administration of AOSs. The detection level of agarobiose in the plasma was higher than that of agarohexaose, which was consistent with the permeation study using Caco-2 cell monolayers. Further, the adenosine triphosphate inhibitor (sodium azide) or endocytosis inhibitor (colchicine) did not inhibit AOS permeation through Caco-2 cell monolayers. Conversely, AOS permeation enhanced upon treatment with cytochalasin B, a tight junction disrupter, suggesting that AOSs might have passed mainly through the tight junctions between the intestinal epithelial cells. These results indicate that AOSs, especially agarobiose, can be absorbed via the gastrointestinal tract across the intestinal epithelium through the paracellular pathway.